Cardiovascular and renal outcomes with canagliflozin according to baseline diuretic use: a post hoc analysis from the CANVAS Program. (17th February 2021) - Yu, Jie; Arnott, Clare; Neuen, Brendon L.; Heersprink, Hiddo L.; Mahaffey, Kenneth W.; Cannon, Christopher P.; Khan, Sadiya S.; Baldridge, Abigail S.; Shah, Sanjiv J.; Huang, Yuli; Li, Chao; Figtree, Gemma A.; et al.
Abstract: Aims: The CANVAS Program identified the effect of canagliflozin on major adverse cardiovascular events (MACE) differed according to whether participants were using diuretics at study commencement. We sought to further evaluate this finding related to baseline differences, treatment effects, safety, and risk factor changes. Methods and results: The CANVAS Program enrolled 10 142 participants with type 2 diabetes mellitus and high cardiovascular risk. Participants were randomized to canagliflozin or placebo and followed for a mean of 188 weeks. The primary outcome was major cardiovascular events, a composite of cardiovascular death, nonfatal myocardial infarction, or nonfatal stroke. Secondary outcomes included multiple cardiovascular, renal, and safety events. In this post hoc subgroup analysis, participants were categorized according to baseline use of any diuretic. The effect on outcomes was compared using Cox proportional hazards models, while risk factor changes were compared using mixed‐effect models. At baseline, 4490 (44.3%) participants were using a diuretic. Compared with those not using a diuretic, participants using a diuretic were more likely to be older (mean age ± standard deviation, 64.3 ± 8.0 vs. 62.5 ± 8.3), be female (38.9% vs. 33.4%), and have heart failure (19.6% vs. 10.3%) (all P difference < 0.0001). The effect of canagliflozin on major cardiovascular events was greater for those using diuretic at baseline than for those who were not [adjusted hazard ratio 0.65 (95% confidence interval 0.54–0.78) vs. adjusted hazard ratio 1.13 (95% confidence interval 0.93–1.36), P heterogeneity < 0.0001]. Changes in most risk factors, including blood pressure, body weight, and urine albumin‐to‐creatinine ratio, were similar between groups (all P difference > 0.11), although the effect of canagliflozin on haemoglobin A1c reduction was slightly weaker in participants using compared with not using diuretics at baseline (−0.52% vs. −0.64%, P heterogeneity = 0.0007). Overall serious adverse events and key safety outcomes, including adverse renal events, were also similar (all P heterogeneity > 0.07). Conclusions: Participants on baseline diuretics derived a greater benefit for major cardiovascular events from canagliflozin, which was not fully explained by differences in participant characteristics nor risk factor changes.